Impact Analysis of Advising and Counseling System for Under-graduation Students in Bangladesh (Global Journal of Computer Science and Technology, 2019)
In the development process of a student, counseling and advising system plays a crucial role. By providing proper counseling through empathetic relationship, we can learn about the problems of a student. With the help of this learning, we can find out all of the negative issues that are happening with the students. Such as- why their results are poor, why they are irregular in their study and many more. Even providing counseling, we can know their weakness, strength, and opportunities. Not only that, but it also helps to build a good relationship between teachers and students. Students can overcome their gap that exists between students and teachers, and that will ensure good bonding among them. So counseling is a must factor to develop a qualified student. Before taking any decision against any student, it2019;s important to learn their present condition through counseling. That2019;s why proper counseling with an effective way is necessary for all students. To understand the effects of counseling and academic advising, we surveyed on Daffodil International University. With this survey, we tried to realize all of the facts related to it. Based on the analysis, we have also mentioned some recommendations which may be helpful for the betterment of the undergraduate students.
Keywords: advising; counseling; questionnaire; group discussion; recommendation